Agricultural chemical use and the rural-urban divide in Canada - Stuart J. Smyth; Sylvain Charlebois (GM Crops & Food)
Innovation is of fundamental importance for improving food production, as well as sustainability food production. Since 1960, food production has benefited from innovations in plant breeding technologies, fertilizer, chemicals and equipment. These innovations have dramatically increased food production, while the amount of land used has minimally increased. However, future food production increases are jeopardized from widening knowledge gaps between rural food producers and large urban food consuming populations. Over time, that gap has fueled disinformation. The development of disinformation business models contributes to urban consumers receiving inaccurate information about the importance of inputs essential to food production, resulting in political pressures being applied that are targeted at reductions in the use of many food production inputs. The use of chemicals are a frequent target of disinformation campaigns. This article examines how the lack of government clarity about the safe use of chemicals contributes to a lack of public information.